Penerapan Metode Waspas dan Aras Dalam Menentukan Biji Kopi Terbaik Untuk Kopi Lain Hati - Yulfanni Br. Tarigan, Ririn; Ramadani (Buletin Ilmiah Informatika Teknologi, 2025)
Coffee beans are the seeds of the coffee plant and are the main source for coffee drinks. In Indonesia, there are two main varieties of coffee beans developed, namely Robusta Coffee (Coffee Robusta) and Arabica Coffee (Coffee Arabica). Coffee is one of Indonesia's main export commodities, occupying the third position in the world after Brazil and Vietnam. This research aims to determine the criteria in determining the selection of quality coffee beans through the Weighted Aggregated Sum Product Assessment (WASPAS) and Additive Ratio Asessment (ARAS) methods. This is done to simplify the process of selecting quality coffee beans. This research uses 5 criteria, namely: Price, Color, Aroma , Taste , and Impurity Content . The results of the study show that the ratings resulting from the application of the two methods have similarities. The best alternative identified after the application of both methods is the C7 alternative. Using the WASPAS method, the C7 alternative obtained a reference value of 0.5255. Meanwhile with the ARAS method, the C7 alternative gets the highest reference value, which is 0.9908.